Analysis of reinforced concrete shear walls with single band of octagonal openings - Marsono, A. K. (2016)
The applications of cast-in-situ reinforced concrete shear walls for tall buildings are prevalent in many countries. Shear walls with openings are called coupled shear walls which act as cantilevered walls joined by coupling beams. Openings for windows and doors affect the behaviour of the structure and cause to decrease the strength of shear wall. Some methods were suggested in the past to increase the strength of shear wall but they are not easy to apply and need labour attentiveness. This study proposes adding haunches to the corners of rectangular openings as a simple method to increase the strength of coupled shear wall structures. Analytical analysis employing Total Moment Concept and Continuous Connection Method (CCM) and Nonlinear Finite Element Analysis (NLFEA) were carried out on symmetrical shear walls with single band of octagonal openings. The results are compared with outputs of previous study on shear wall with rectangular openings. The analysis results demonstrated that it is confidently worth to use the octagonal openings due to very small percentage increase in the total weight of the structure compared with the amount increase in ultimate load of the shear walls.